Habitat Structure Influences Parent-Offspring Association in a Social Lizard - Botterill-James, Thomas; Halliwell, Ben; Cooper-Scott, Emily; Uller, Tobias; Wapstra, Erik; While, Geoffrey M. (Frontiers in Ecology and Evolution, 2016)
Parental care emerges as a result of an increase in the extent of interaction between parents and their offspring. These interactions can provide the foundation for the evolution of a range of complex parental behaviors. Therefore, fundamental to understanding the evolution of parental care is an understanding of the factors that promote this initial increase in parent-offspring association. Here, we used large outdoor enclosures to test how the spatial structure of high-quality habitat affects the occurrence of parent-offspring associations in a social lizard (Liopholis whitii). We found that the extent of parent-offspring association was higher when high-quality habitat was aggregated relative to when it was dispersed. This may be the result of greater competitive exclusion of adults and offspring from high quality crevices sites in the aggregated treatment compared to the dispersed treatment. Associating with parents had significant benefits for offspring growth and body condition but there were no concomitant effects on offspring survival. We did not find costs of parent-offspring association for parents in terms of increased harassment and loss of body condition. We discuss a number of potential mechanisms underlying these results. Regardless of mechanisms, our results suggest that habitat structure may shape the extent of parent-offspring association in L. whitti, and that highly aggregated habitats may set the stage for the diversification of more complex forms of care observed across closely related species.